ANALYSIS BUSINESS OPPORTUNITIES MELALUI BUDIDAYA JAMUR TIRAM PUTIH PADA DATARAN RENDAH PADA CV. KEMUNING BANGKALAN MADURA - Maulidyah Amalina Rizqi (JURNAL MANAJERIAL, 2017)
Geographical and agricultural conditions exist in the Madura Island that the Madura Island is an area with hot temperatures and has a low rainfall. This research was conducted in the tropics with little rainfall, this study also looked at whether the location intended by the researchers could be used to carry out the process of cultivating oyster mushrooms and whether this effort could continue to be developed. This research used a qualitative paradigm approach to provide an aspect of flexibility in gathering information from informants about the development of oyster mushroom cultivation. The results of this research can be seen cultivation of white oyster mushroom can be done in lowland area with the supporting factors such as land, water resources and other support. This cultivation business can be done by all gender. The potential or business opportunities through the cultivation of white oyster mushrooms in low areas is very large because the results obtained can be doubled from the capital that must be issued by the business. Actually we can get more profit if farmers can be more creative by processing white oyster mushrooms into processed products that have added value then the farmers will also get bigger results again, not even just doubled but can be many times over. Because the real business should be able to think creative and innovative.